1934
DOI: 10.1017/s0021859600007280
|View full text |Cite
|
Sign up to set email alerts
|

The determination of winter-hardiness in oats

Abstract: When assessing the value of any variety of a commercial plant one is concerned with a number of different features of the plant's behaviour, among others winter-hardiness. The behaviour with regard to most of these features is tested by methods which have been carefully planned and whose reliability has been proved, but the determination of winter-hardiness is still a matter of observing the reaction of the plants to the conditions prevailing at that season of the year. However, in England, particularly in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1935
1935
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…High correlations between .survival of wheats in artificial freezing tests and survival under field conditions have been reported by Martin ( 6), Quisenberry ( 10), Wiebe I and Quisenberry ( 12), and others. Mather and Anderson ( 7) concluded that artificial freezing tests of oat varieties in England and Sweden pro• vided a real test of the winterhardiness of the varieties. Murphy et al (9) employed artificial refrigeration in the selection of winter-hardy and disease resistant oat lines.…”
mentioning
confidence: 99%
“…High correlations between .survival of wheats in artificial freezing tests and survival under field conditions have been reported by Martin ( 6), Quisenberry ( 10), Wiebe I and Quisenberry ( 12), and others. Mather and Anderson ( 7) concluded that artificial freezing tests of oat varieties in England and Sweden pro• vided a real test of the winterhardiness of the varieties. Murphy et al (9) employed artificial refrigeration in the selection of winter-hardy and disease resistant oat lines.…”
mentioning
confidence: 99%